2011
DOI: 10.1051/fruits/2011048
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics of bisir ‘Barhee’ dates during cold storage as affected by postharvest dipping in gibberellic acid, naphthaleneacetic acid and benzyladenine

Abstract: Quality characteristics of bisir 'Barhee' dates during cold storage as affected by postharvest dipping in gibberellic acid, naphthaleneacetic acid and benzyladenine.Abstract -Introduction. There is a growing demand in the international market for excellent-quality dates of cultivars such as 'Barhee' that are consumed at the bisir stage. Materials and methods. The effects of GA 3 , BA and NAA postharvest dipping treatments at different concentrations on the quality characteristics of bisir 'Barhee' dates during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 12 publications
4
17
0
Order By: Relevance
“…The amount of Malic acid of both flesh date varieties increases with a significant manner with final concentration ranging of 0.300% for Majhoul and 0.278% for Boufeggous (Table ). These results are in conformation with the study of Al‐Qurashi and Awad (). These authors' reports that acidity level of date fruits increased slightly under cold storage conditions for Bisir ‘Barhee’ dates.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The amount of Malic acid of both flesh date varieties increases with a significant manner with final concentration ranging of 0.300% for Majhoul and 0.278% for Boufeggous (Table ). These results are in conformation with the study of Al‐Qurashi and Awad (). These authors' reports that acidity level of date fruits increased slightly under cold storage conditions for Bisir ‘Barhee’ dates.…”
Section: Resultssupporting
confidence: 91%
“…These results confirm the findings of Al‐Qurashi and Awad () who reported an increase in ‘Barhee’ date fruit weight loss (%) compared with control fruit when stored at 1°C for 2 months.…”
Section: Resultssupporting
confidence: 91%
“…Date fruits maturation goes through five stages: Hababouk, Kimri, Khalal (Bisir), Rutab and Tamer Figure [1] . Normally, dates are harvested and marketed at the last three stages of maturity and can be consumed soft, semi-dry or as dry fruits, depending on cultivar features, climatic conditions and market demand [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Dipping in GA 3 prior to storage is applied to a wide range of fruits and achieved good results in quality preservation. Al-Qurashi and Awad [9] reported that postharvest dipping in GA 3 inhibited ripening and slightly improved the quality of cold stored Barhi dates at Khalal (bisir) stage. In addition, GA 3 at 150 ppm concentration significantly slowed down rate of fruit color changing and softening.…”
Section: Introductionmentioning
confidence: 99%
“…These phases of maturity are associated with distinctive texture, sensory and chemical attributes (Awad, Al‐Qurashi, & Mohamed, ; Mehyar, El Assi, Alsmairat, & Holley, ). Date fruits is consumed while in Khalal, Rutab and Tamer stages and this depends on factors such as amount of soluble tannins in the cultivars, market demand and climate conditions (Al‐Qurashi & Awad, ; Glasner, Botes, Zaid, & Emmens, ). Barhi is a popular date fruit variety and its Khalal stage (sweet taste and yellow color) is short after harvest (August‐September in Saudi Arabia) and changes to Rutab in around 1 week if not handled properly.…”
Section: Introductionmentioning
confidence: 99%